MicroRNA-7 targets T-Box 2 to inhibit epithelial-mesenchymal transition and invasiveness in glioblastoma multiforme. (28th November 2020) - Pan, Chih-Ming; Chan, Kai-Hsiang; Chen, Chao-Hsuan; Jan, Chia-Ing; Liu, Ming-Chao; Lin, Chien-Min; Cho, Der-Yang; Tsai, Wan-Chen; Chu, Yen-Tse; Cheng, Cheng-Hsin; Chuang, Hao-Yu; Chiu, Shao-Chih
Abstract: The dysregulation of microRNA expression in cancer has been associated with the epithelial-mesenchymal transition (EMT) that triggers invasive ability and increases therapeutic resistance. Here, we determined the microRNA expression profile of seven tumor tissues from patients with glioblastoma multiforme (GBM) by use of microRNA array analysis. We discovered that microRNA-7 (miR-7) is consistently downregulated in all tumor samples. Using the microRNA.org algorithm, the T-box 2 gene (TBX2) was identified as a candidate gene targeted by miR-7. In contrast to miR-7, TBX2 had an increased expression in GBM tumors and was linked to poor prognosis. We confirmed that TBX2 mRNA and protein production are significantly repressed by overexpressing miR-7 in GBM cells in vitro . The reporter assay showed that miR-7 significantly represses the signal from luciferase with the 3′ UTR of TBX2. Furthermore, TBX2 overexpression decreased E-cadherin expression and increased Vimentin expression, causing an increasing number of invaded cells in the invasion assay, as well as pulmonary metastasis in vivo . Our findings demonstrated that overexpression of TBX2 in GBM tumors via the downregulation of miR-7 leads to EMT induction and increased cell invasion. Highlights: MicroRNA-7 is reduced in glioblastoma tumors. TBX2 is identified as a target for microRNA-7. TBX2 increases in glioblastoma due to decreased microRNA-7 and patients with high TBX2 expression have a poor prognosis. TBX2 enhances the invasiveness of glioblastoma cells and promotes pulmonary metastasis in vivo . TBX2 expression was associated with EMT features in tumor tissues.